Weather Information for Garden City, 2019 - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2020)
Summary of 2019 weather for research conducted at the Garden City field location.
Keywords: Garden City weather; 2019 weather; southwest Kansas weather report